Encapsulation of trichloroacetic acid and trifluoroacetic acid for autonomous self healing coatings - KAHRAMAN, MEMET VEZİR (TAYLOR & FRANCIS INC, 2020)
Microcapsules with TFA or TCA healing agents with an outer poly(melamine-urea-formaldehyde) (PMUF) were successfully synthesized for the first time, according to a review of published literature. The average sizes of the microcapsules obtained were measured to be 1.7 and 2 mu m for TFA/PMUF and TCA/PMUF, respectively. Both microcapsules were separately added to an epoxy-based coating formulation. To examine the self-healing properties, scanning electron microscopy images were examined at the moment that damage occurred and seven days later. A self-healing experiment showed that the more reactive PMUF/TFA microcapsules were more efficient than the PMUF/TCA microcapsules in repairing scratch damage in the coatings.
Keywords: PMUF microcapsules; trifluoroacetic acid; trichloroacetic acid; self-healing; epoxy-based coatings; MELAMINE-UREA-FORMALDEHYDE; POLY(UREA-FORMALDEHYDE) MICROCAPSULES; LINSEED OIL; EPOXY; MICROENCAPSULATION; FABRICATION; DESIGN; AGENT; AMINE; RESIN